The current relevance of three classical cases of social science research ethics: Milgram, Humphreys and Zimbardo - Santi, María Florencia (2024)
Background: Research ethics in social sciences is of great relevance for the protection of participants.Objectives: Conduct an ethical analysis of three classic cases of social science research: Milgram´s experiment of obedience to authority; Humphreys´ tearoom trade and Zimbardo´s prison experiment.Methods: A problematic ethical analysis of the cases was carried out. The main ethical debates raised by the cases were reconstructed in their historical context and the ethical issues were considered from a current perspective.Results: The relevance of the ethical analysis of the classic cases of research ethics in social sciences and the relevance of carrying out an ethical analysis from the current concepts of research ethics were shown.Conclusion: The need for an independent ethical evaluation of ethical issues was revealed in order to adequately understand and evaluate social science research and its methodological richness.